2006
DOI: 10.1074/jbc.m508955200
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Leucyl Aminopeptidase in Plasmodium falciparum Parasites

Abstract: Malaria aminopeptidases are important in the generation and regulation of free amino acids that are used in protein anabolism and for maintaining osmotic stability within the infected erythrocyte. The intraerythrocytic development of malaria parasites is blocked when the activity of aminopeptidases is specifically inhibited by reagents such as bestatin. One of the major aminopeptidases of malaria parasites is a leucyl aminopeptidase of the M17 family. We reasoned that, when this enzyme was the target of bestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 37 publications
1
52
0
Order By: Relevance
“…Our report of the unique active site structure of PfA-M1, in complex with the antimalarial inhibitors bestatin and Co4, provides the groundwork for the de novo discovery of a previously unrecognized class of antimalarials by using high-throughput chemical screening and medicinal chemistry. Co4 also inhibits the second important neutral aminopeptidase of malaria, PfA-M17 (12,26), creating the possibility of developing a 2-target or combination therapy that would be more resilient to the emergence of drug-resistant malaria parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Our report of the unique active site structure of PfA-M1, in complex with the antimalarial inhibitors bestatin and Co4, provides the groundwork for the de novo discovery of a previously unrecognized class of antimalarials by using high-throughput chemical screening and medicinal chemistry. Co4 also inhibits the second important neutral aminopeptidase of malaria, PfA-M17 (12,26), creating the possibility of developing a 2-target or combination therapy that would be more resilient to the emergence of drug-resistant malaria parasites.…”
Section: Discussionmentioning
confidence: 99%
“…A widely cited model holds that the terminal stages of hemoglobin degradation occur in the cytosol, with peptides exported from the FV for hydrolysis by cytosolic aminopeptidases (11,12). This model is based largely on the apparent lack of aminopeptidase (AP) activity in extracts of enriched FVs (12), on the localization of two P. falciparum APs to the cytosol (13)(14)(15), and on the apparent absence of carboxypeptidase homologs from the annotated parasite genome sequence (16). Support for this model is weakened, however, by the absence of experimental evidence for peptide export from the FV, and by the presence of uncharacterized AP homologs in the P. falciparum genome sequence that could play a role in vacuolar peptide catabolism.…”
mentioning
confidence: 99%
“…PfM17LAP was detected as a 68-70 kDa protein in soluble extracts of P. falciparum malaria parasites, immunocytochemical studies located the enzyme to the parasite cytoplasm. 41,52 This location has been confirmed by confocal microscopy of live transfected parasites expressing fluorescently-tagged PfM17LAP 30,41,52 . Using specific inhibitors of PfM17LAP, Harbut et al 45 showed that killing of P. falciparum in culture occurs early in the intraerythrocytic cycle (ring stages) prior to the onset of significant haemoglobin digestion suggesting that this enzyme does not play a part in this process.…”
Section: Do Pfm1aap and Pfm17lap Function In The Same Or Different Cementioning
confidence: 75%
“…30,34 We also generated transgenic P. falciparum parasites that over-expressed functionally active aminopeptidases in the cytoplasm and showed that these parasites were less susceptible to killing by bestatin (1) and hPheP[CH 2 ]Phe (3) when compared to wild-type parasites. 42,52 These data imply that both PfM1AAP and PfM17LAP are targets for the anti-malarial activity of these two broad-spectrum aminopeptidase inhibitors. Since most inhibitors used in the study of the malaria aminopeptidases block the activity of both PfM1AAP and PfM17LAP it remained unclear from reported in vitro and in vivo tests whether one or both enzymes was the targets of the aminopeptidase inhibitor-mediated killing of malaria parasites.…”
Section: Are Pfm1aap and Pfm17lap Targets For Anti-malarial Drug Devementioning
confidence: 98%